Climate-Smart Agriculture in Asia: Beyond pilot evaluations and models (Workshop Proceedings) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The proceedings document the highlights of the Climate-Smart Agriculture in Asia workshop, sponsored by the CCAFS programs in Southeast Asia and South Asia. The event was organized to bring together key stakeholders to discuss and exchange learnings in order to achieve the following objectives: 1) identify scalable CSA options and methods of scaling them, especially those related to technologies, climate information services, and insurance; 2) identify key selling points of CSA and its value for banks and development partners; and 3) establish ways to make CSA R4D responsive to upscaling and big investment in Asia.